PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI METODE PEMBELAJARAN EDUTAINMENT PADA ANAK KELOMPOK B DI TK AL-KAUTSAR INDRALAYA - Cahya Yunisari; Sri Sumarni; syafdaningsih syafar (FKIP Universitas sriwijaya, 2017)
This study aims to improve fine motor skills through edutainment learning methods in children group B in Al Kautsar Indralaya Kindergarten. The method used in this research is Classroom Action Research. The subjects of this study were children aged 5-6 years, amounting to 13 children consisting of 5 boys and 8 girls. This research instrument uses observation sheet. The results of data analysis showed an increase in the number of children who reached the limit of classical completeness of cycle I and cycle II in a row. There are number of children who get a minimum score of 63 in the category of Expectant Expectations (BSH) that is in cycle 1 as many as 9 children (69%), then increased in cycle II as many as 12 children (92%). This is evidenced by all indicators emerging from the observation at the end of cycle II that all children move fingers, inflating both cheeks, moving hands, and moving both eyes. From the data collected indicate that there is improvement of fine motor ability of child of group B at Al-Kautsar Indralaya Kindergarten after using Edutainment Learning Method.